Penanganan Perilaku Mudah Marah pada Anak Akibat Game Online melalui Teknik Self Control dalam Layanan Bimbingan dan Konseling - Graeny Andini Paseru; Delsi Mona Kombong; Kurnia Bato Kendek (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to provide a detailed overview of efforts in counseling and guidance programs that teach self-control skills to children whose gaming habits are causing problems. When children spend too much time playing online video games, it can negatively impact their mental health. Problems with emotional regulation, irritability, and lack of self-control in daily life are possible consequences. Appropriate counseling and guidance services are needed to help children develop more adaptive skills to manage their emotions. This study used extensive qualitative data and followed a case study technique. A child whose gaming addiction was causing problems for him participated in the study. Data analysis included tasks such as data reduction, data presentation, and drawing conclusions; data collection methods included documentation, interviews, and observation. Based on the findings, guidance and counseling programs can teach children self-control strategies to help them manage their emotions, reduce irritation, and become more self-aware when playing online games. Therefore, teaching children self-control skills may be a good way to help them overcome negative feelings that arise from playing online video games.